PERSEPSI PESERTA DIDIK TENTANG PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) MATA PELAJARAN BIOLOGI - Munir, Asmawati; Sabilu, Murni; Nurfadilla (Jurnal Biogenerasi, 2025)
This study aims to determine the perceptions of independent class XI students about the Pancasila Student Profile Strengthening Project (P5) in Biology at SMAN 3 Kendari. P5 is part of the Independent Curriculum which aims to integrate Pancasila values into learning through a project-based approach. One of the projects studied is "Beauty from Plastic", which examines the issue of plastic waste management as a creative product relevant to biology material on pollution and environmental preservation. This study uses a survey method with a quantitative descriptive approach, using a questionnaire instrument (google form) in the form of a Likert scale. Data were distributed to 259 independent class XI students, in this study using Purposive sampling with a sampling technique with certain considerations, so the sample was 198 respondents. The research instrument was tested for validity and reliability. Analyzed using descriptive statistics, then frequency distribution analysis to determine the position of perception. The Pancasila Student Profile Strengthening Project (P5) in Biology at SMAN 3 Kendari has variations in perception, namely high, medium, and low perceptions. The results of the study showed that the highest percentage of understanding indicators was in the high category at 67%, the highest percentage of acceptance indicators was in the high category at 52%, and the highest percentage of evaluation indicators was in the high category at 49%. The perceptions of independent class XI students regarding the Pancasila Student Profile Strengthening Project (P5) in Biology subjects at SMAN 3 Kendari were generally in the High category.